Surfactant Assisted Stabilization of Carbon Nanotubes Synthesized by a Spray Pyrolysis Method - D. Mendoza-Cachú; C. Mercado-Zúñiga; G. Rosas (Advances in Condensed Matter Physics)
Surface modification of carbon nanotubes has been an interesting issue from a composites materials point of view. A nanotubes agglomeration has to be avoided to achieve a homogeneous dispersion in a composite matrix. In this research, we report on the synthesis of carbon nanotubes using a variant of the chemical vapor deposition technique known as spray pyrolysis method. X-ray diffraction (XRD), transmission electron microscopy (TEM), and scanning electron microscopy (SEM) studies showed that the synthesized products had an aligned structure with low purity degree, high content of catalyst particles, and a smaller amount of amorphous carbon. A secondary method was applied, which involves an acidic treatment that dissolves contaminant particles to enhance the purity of the nanotubes. Microstructural analysis, which includes XRD and SEM, indicates an effective reduction of impurities. Dispersion of the nanotubes was assessed using different surfactants, such as sodium dodecyl-sulfate (SDS) and ethylenediaminetetraacetic acid (EDTA). Finally, Raman spectroscopy, UV-Vis, and SEM techniques confirm that better results were obtained with EDTA. For EDTA and SDS surfactants, low concentrations of 0.3 mg/mL and 0.2 mg/mL were most efficient, respectively.